2022
DOI: 10.1007/s11162-022-09679-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Early-Career University Prestige Stratification on the Future Academic Performance of Scholars

Abstract: This paper investigates the effect of university prestige stratification on scholars’ career achievements. We focus on 766 STEM PhD graduates hired by Mexican universities between 1992 and 2016. We rank university according to their prestige based on the pairwise assessment of quality contained in the PhD hiring networks. Further, we use a quasi-experimental design matching pairs of individuals with the same characteristics, PhD training or first job experience. Our results challenge the positive association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…Overall the analysis of enrolment outcomes highlights a negative impact of the decrease in government appropriation of PhD scholarships on the entry rate of females and nontraditional students with effect that persists for a decade after the cuts. This is not surprising given the well-known inertia and stratification of university systems in general and of those of emerging economies in particular (Rossello, 2021;Cowan and Rossello, 2018;González-Sauri and Rossello, 2023). (2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall the analysis of enrolment outcomes highlights a negative impact of the decrease in government appropriation of PhD scholarships on the entry rate of females and nontraditional students with effect that persists for a decade after the cuts. This is not surprising given the well-known inertia and stratification of university systems in general and of those of emerging economies in particular (Rossello, 2021;Cowan and Rossello, 2018;González-Sauri and Rossello, 2023). (2021).…”
Section: Resultsmentioning
confidence: 99%
“…3 There are some exceptions but in general tuition when present is very low, and international students are charged more between 1,200 and 5,000 a year. See this website for an overview https://www.masterspor tal.com/articles/2871/tuition-fees-and-living-costs-in-hungary-in-2023.ht ml; accessed June 2023. listed in international rankings and their perceived prestige can be volatile, as found in other emerging economies (González-Sauri and Rossello, 2023). Second, the specific case of the Hungarian universities after the second election of Orbán represents a perfect setting.…”
Section: Introductionmentioning
confidence: 99%
“…Their research suggests that stars may receive preferential treatment within their institutions but do not necessarily demonstrate more success than peers who do not benefit from being perceived as stars. Gonzales-Sauri and Rossello (2023) concluded that promising scholars who move to more prestigious institutions do not then demonstrate greater success than those who move to less prestigious institutions. Although prominent academics do seem to benefit from reputational gains, there is no evidence that they no longer need developmental supports as they continue to advance in their careers.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…For example, Bihagen et al explored gender differences in occupational maturity in Sweden [53], while Light focused on the intrinsic relationship between gender stratification and publishing in American science [54]. Gonzá lez-Sauri et al investigated the influence of early-career academic prestige stratification on scholars' future academic achievements [55]. Furthermore, Posselt et al discussed the relationship between graduate education and social stratification [56], and Canche delved into the salary disparities among community college scientists [57].…”
Section: The Essence Of Scientific Social Stratification: Unifying Ac...mentioning
confidence: 99%